CNCs modification method

By performing GMA modification in CNCs aqueous solution and introducing AAm copolymerization, CNCs-GMA@PAAm gel material is formed, and the problem of low functionality of existing CNCs modification methods is solved, and diversified detection of CNCs and broadening application fields are achieved.

CN119613622APending Publication Date: 2025-03-14EAST CHINA UNIV OF SCI & TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411706414.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing CNCs modification methods have problems such as low functionality, single detection strategy, and limited detection type, which is difficult to broaden the detection range and application fields of CNCs.

Method used

Chemical modification is performed by adding GMA to the CNCs aqueous solution, GMA is grafted onto the surface of CNCs to form an aqueous CNCs-GMA solution, and AAm is introduced on the basis for copolymerization and co-assembly to form a CNCs-GMA@PAAm gel material, giving it additional chemical properties and solvent responsiveness.

Benefits of technology

The stability and optical properties of CNCs are achieved, while giving them new chemical properties and solvent responsiveness, broadening their detection range and application fields, especially in the field of molecular detection, providing new possibilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613622A_ABST
    Figure CN119613622A_ABST
Patent Text Reader

Abstract

The invention relates to a CNCs modification method. The CNCs modification method comprises the following steps: S1, preparing a CNCs aqueous solution; and S2, GMA is added into the CNCs aqueous solution for chemical modification, hydroxyl groups of the CNCs and epoxy groups of the GMA are subjected to a ring-opening reaction, so that the GMA is grafted to the surfaces of the CNCs to form a CNCs-GMA aqueous solution, and carbon-carbon double bonds of the GMA are reserved and introduced into a CNCs-GMA structure. According to the CNCs modification method, a more advanced CNCs stimulation response system can be obtained, the stability of the material can be guaranteed, additional chemical properties can be given, the method can be used for preparing a CNCs photonic crystal sensor, the detection range of CNCs is widened, new possibility and thought are provided for CNCs in the field of molecular detection, and then the application field of CNCs is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to chemical modification, and more particularly to a CNCs modification method. Background Art

[0002] Cellulose nanocrystals (CNCs) are a type of photonic crystal material that has the ability to selectively reflect visible light. When the wavelength of the reflected visible light is within the visible light range, the CNCs optical film can show a structural color covering the entire visible light region, and the structural color is affected by the parameters in the preparation process of CNCs. By adjusting the parameters, CNCs can be strictly controlled within each color in the visible light region, including blue, green and even red. This color controllability visible to the naked eye has enabled CNCs to be fully applied and developed in the field of stimulus sensing. Based on the adjustable optical properties of CNCs, it has achieved considerable research results in optical responsiveness detection, and the detection content is not limited to pH, vacuum, mechanical external force, relative humidity, organic solvents and some gas small molecules. However, due to the poor mechanical strength and solvent resistance of CNCs themselves, its detection strategy is single and the type of detection objects is limited. Therefore, it is urgent to develop new CNCs chemical modification methods, broaden CNCs detection strategies, and realize the diversification of detection molecules, so as to prepare new CNCs-based molecular detection photonic crystal sensors.

[0003] Since CNCs have a large number of hydroxyl sites, they can be modified to different degrees according to the active chemical properties of the hydroxyl groups. The modified CNCs still have good aqueous solution stability, and most importantly, they can maintain the same crystal structure and chiral nematic liquid crystal structure as the original CNCs. The modified CNCs can be used as a hydrogel monomer, making them more widely used in the field of stimulus responsive detection.

[0004] At present, the modification methods of CNCs are mainly divided into two methods: physical blending and chemical modification. The former is to mix the CNC suspension with some functionalized molecules by stirring, and then co-assemble to form a photonic crystal composite film; the latter is to link CNCs with other materials through chemical reactions between functional groups, but most of the methods of chemically modifying CNCs are based on the addition of intermediates. The intermediates here play a "bridge role" and are responsible for connecting CNCs with modified molecules to form photonic crystal composite materials. However, the modification method of physical blending often has problems such as simple system components and low functionality. The modification of CNCs itself in the chemical modification method is not common. Therefore, it is necessary to construct a chemical modification method that can not only not destroy the optical structure of CNCs, but also introduce new functional groups into CNCs to achieve chemical modification. Summary of the invention

[0005] In order to solve the problems of low functionality of the physical and chemical modification in the above-mentioned prior art, the present invention provides a CNCs modification method.

[0006] According to the CNCs modification method of the present invention, it includes the following steps: S1, preparing a CNCs aqueous solution; and S2, adding GMA to the CNCs aqueous solution for chemical modification, wherein the hydroxyl groups of CNCs and the epoxy groups of GMA undergo a ring-opening reaction, so that GMA is grafted onto the surface of CNCs to form a CNCs-GMA aqueous solution, and the carbon-carbon double bonds of GMA are retained and introduced into the CNCs-GMA structure.

[0007] The modified CNCs not only have high aqueous solution stability, but the introduction of GMA does not destroy the original structure of CNCs, retains the crystal structure and adjustable optical properties of cellulose of the original CNCs, but also gives the chemical properties of carbon-carbon double bonds, achieving the purpose of modification while expanding its application range through the chemical reactivity of double bonds.

[0008] In a preferred embodiment, in step S1, a cellulose raw material is hydrolyzed by sulfuric acid to obtain a CNCs aqueous solution. Specifically, CNCs are prepared by dehydrating pulp by sulfuric acid hydrolysis and by standing, centrifuging, dialysis and tip ultrasound. In a preferred embodiment, the cellulose raw material is microcrystalline cellulose or obtained by fully mixing qualitative filter paper with water and then crushing and drying.

[0009] In a preferred embodiment, step S1 includes the following sub-steps: S11, hydrolyzing the amorphous regions in the cellulose raw material with sulfuric acid, leaving the crystalline regions to provide a basis for forming CNCs; S12, dialysis to remove excess sulfuric acid and small molecule impurities; and S13, centrifugation to remove incompletely hydrolyzed cellulose raw material.

[0010] In a preferred embodiment, the CNCs aqueous solution in step S1 self-assembles into a CNCs optical film with a cholesteric liquid crystal structure.

[0011] In a preferred embodiment, in step S2, an acid is added to the CNCs aqueous solution to adjust its pH to 3.0, and then GMA is added, mixed and stirred to obtain a CNCs-GMA aqueous solution. Specifically, the CNCs aqueous solution and GMA are stirred at a temperature of 50°C to 70°C at a speed of 400rpm to 500rpm, and then dialyzed through a dialysis bag to obtain a CNCs-GMA aqueous solution. In a preferred embodiment, the molecular weight cutoff of the dialysis bag is 14,000, the dialysis time is about 3 days, and the water is changed at least three times a day during the dialysis process.

[0012] In a preferred embodiment, the CNCs modification method further includes adding AAm to the CNCs-GMA aqueous solution for copolymerization and co-assembly, and introducing CNCs into the three-dimensional network of polyacrylamide hydrogel to obtain CNCs-GMA@PAAm. Specifically, AAm monomers are polymerized to form polyacrylamide PAM chains, and CNCs-GMA participates in the polymerization reaction as comonomers to form CNCs-GMA@PAAm gel composite materials. In this way, the present invention innovatively introduces GMA-modified CNCs into the polyacrylamide hydrogel network, and CNCs-GMA@PAAm has good solvent responsiveness, further expanding its scope of application.

[0013] In a preferred embodiment, AAm, Bis and PI are dissolved in a CNCs-GMA aqueous solution, co-assembled by volatilization induction, and then irradiated under ultraviolet light to achieve photopolymerization to obtain a CNCs-GMA@PPAm gel material.

[0014] In a preferred embodiment, the mass ratio of AAm, Bis and PI is 100:10:1. In a preferred embodiment, the volatilization is carried out in a polystyrene plastic dish. In a preferred embodiment, the irradiation is carried out for 10 minutes to achieve photopolymerization.

[0015] In a preferred embodiment, in step S2, the CNCs-GMA aqueous solution is used to prepare a CNCs-GMA optical film by evaporation-induced self-assembly. Specifically, the dialyzed CNCs-GMA aqueous solution is placed in a polystyrene plastic (PS) dish to evaporate the solvent, and then the CNCs-GMA optical film is directly formed.

[0016] In a preferred embodiment, the CNCs modification method further includes introducing FPBA that interacts with glucose into the three-dimensional network of polyacrylamide hydrogel using a photoinitiator strategy to obtain CNCs-GMA@PAAm-FPBA. Specifically, FPBA is a phenylboronic acid derivative with a carbon-carbon double bond, and also participates in the polymerization reaction as a comonomer. In this way, the present invention innovatively introduces GMA-modified CNCs and FPBA into the hydrogel network at the same time to achieve glucose molecule detection, has good molecular detection responsiveness, and further expands its application range.

[0017] In a preferred embodiment, AAm, Bis, PI and FPBA are added to DMSO and dissolved to obtain a hydrogel monomer solution containing FPBA, and the CNCs-GMA optical film is fully immersed and swelled in pure DMSO solution and a hydrogel monomer solution containing FPBA, respectively, and irradiated under ultraviolet light to achieve photoinitiated polymerization, and then dried to obtain a CNCs-GMA@PAAm-FPBA optical composite material.

[0018] In a preferred embodiment, the mass ratio of AAm, Bis and PI is 100:10:1.

[0019] According to the CNCs modification method of the present invention, a more advanced CNCs stimulus response system can be obtained, which can not only ensure the stability of the material, but also impart additional chemical properties, and can be used to prepare CNCs photonic crystal sensors, broaden the detection range of CNCs, and provide new possibilities and ideas for CNCs in the field of molecular detection, thereby expanding the application field of CNCs. The raw materials used are simple in source, low in cost, not easy to cause environmental pollution, and the entire experimental process is simple, convenient, and safe to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It shows that by changing the parameters, the color range of CNCs can cover the entire visible light region.

[0021] Figure 2 The aqueous solution stability of CNCs-GMA under different modification conditions is shown.

[0022] Figure 3 Shown are the Fourier transform infrared spectra of CNCs-GMA under different modification conditions.

[0023] Figure 4 Shown are the NMR spectra of CNCs-GMA under different modification conditions.

[0024] Figure 5 Shown are the X-ray diffraction spectra of CNCs-GMA under different modification conditions.

[0025] Figure 6 Shows the polarizing microscope images of CNCs-GMA under different modification conditions.

[0026] Figure 7 Showing the solvent responsiveness of CNCs-GMA@PPAm.

[0027] Figure 8 The responses of CNCs-GMA@PPAm-FPBA under different glucose concentrations and different treatment times are shown. DETAILED DESCRIPTION

[0028] The preferred embodiments of the present invention are given below in conjunction with the accompanying drawings and described in detail.

[0029] Example 1

[0030] Preparation of CNCs aqueous solution: Cellulose nanocrystals (CNCs) obtained by sulfuric acid hydrolysis

[0031] Mix 5g of qualitative filter paper with water, crush the mixture with a pulverizer, and dry it in an oven at 60°C for later use. Mix 98% concentrated sulfuric acid with deionized water in a volume ratio of 1:1 and dilute it to a sulfuric acid solution with a mass concentration of 64%, cool it to room temperature, and the total volume of the solution is 100ml. Then use a water bath or oil bath to heat the diluted sulfuric acid to between 45°C and 50°C, slowly add the dried pulp, keep the temperature unchanged, and stir at 200rpm for 1 hour. Then add 10 times the volume of the solution of cold water to terminate the reaction, let the cooled reactant stand for at least 12 hours to achieve solution stratification, take the lower layer of suspension and centrifuge it at 8000rpm for 15 minutes, collect it and redisperse it in deionized water, and then transfer it to a dialysis bag for dialysis (dialysis bag molecular weight cutoff: 14000) for 3-5 days, and change the water at least three times every 24 hours to remove excess sulfuric acid and small molecule impurities. The dialyzed suspension was centrifuged at 8000 rpm for 10 minutes to remove the incompletely hydrolyzed cellulose fibers in the form of precipitation, and the supernatant was collected to obtain a relatively pure CNCs suspension.

[0032] Preparation of CNCs optical films: CNCs aqueous solution self-assembles into cholesteric liquid crystal structure

[0033] The CNCs suspension prepared as above is subjected to tip ultrasonic treatment to obtain a CNCs optical film having a cholesteric chiral nematic solute liquid crystal.

[0034] In the process of preparing CNCs optical films, by controlling the tip ultrasonic power at 50w, 65w, 80w, 100w and 150w, CNCs optical films with different reflectivity were prepared and their reflectivity was measured by UV spectrum test, such as Figure 1 The results show that as the ultrasonic power increases, the maximum reflection peak of the CNCs optical film red shifts.

[0035] Preparation of CNCs-GMA optical film: GMA was added to the CNCs aqueous solution for modification, so that GMA was grafted onto CNCs-GMA system formed on the surface of CNCs

[0036] The CNCs suspension prepared above was concentrated by a rotary evaporator, and the temperature of the rotary evaporator was controlled below 50°C. The CNCs suspension with a higher concentration was concentrated to 1 / 4 of the original volume to obtain the desired CNCs suspension. Take 5.5 ml of the concentrated CNCs suspension and perform a tip ultrasound with a power of 100w for 5 minutes. Concentrated hydrochloric acid was prepared into a 0.2mM hydrochloric acid solution, and the pH of the CNCs suspension was adjusted to about 3.0, and then 1.0ml GMA was added, and the mixed solution was stirred for 20 hours in a 60°C water bath at 500rpm. The mixed solution after the reaction was placed in a dialysis bag for 3 days (molecular weight cutoff: 14000), and then filtered overnight to remove excess GMA. Collect the CNCs-GMA solution after dialysis, take 2ml and place it in a PS dish with a radius of 2cm, and form a CNCs-GMA optical film after all the solvents are removed.

[0037] In the process of modifying CNCs with GMA, the reaction time was controlled to be 14 h, and 0.5 ml, 0.6 ml, 0.7 ml, 0.8 ml, 0.9 ml and 1.0 ml of GMA solution were added respectively, and the aqueous solution stability of the prepared CNCs-GMA aqueous solution was measured respectively, such as Figure 2 As shown, it shows that the modified CNCs aqueous solution still has good aqueous solution stability. Figure 3 Fourier transform infrared spectroscopy and Figure 4 The nuclear magnetic resonance hydrogen spectrum of the modified CNCs-GMA was determined by X-ray diffractometer, such as Figure 5 As shown, it shows that the modified CNCs still have the original cellulose crystal structure and still have the ability to self-assemble into a cholesteric liquid crystal structure. From the polarizing microscope image, it can be seen that the modified CNCs have a chiral nematic liquid crystal structure, such as Figure 6 shown.

[0038] Preparation of CNCs-GMA@PPAm: AAm was added to the CNCs-GMA system for copolymerization and co-assembly. Into the three-dimensional network of polyacrylamide hydrogel

[0039] Take the prepared CNCs-GMA aqueous solution, weigh acrylamide (AAm), N,N-methylenebisacrylamide (Bis) and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (PI) and add them to the CNCs-GMA aqueous solution until fully dissolved, keeping the ratio of AAm, Bis and PI at 100:10:1. The mixture solution is placed in a polystyrene plastic dish with a radius of 2 cm and evaporated to dryness for co-assembly, and then irradiated under ultraviolet light for 10 minutes to achieve photopolymerization, and then the CNCs-GMA@PPAm gel material is obtained.

[0040] The solvent responsiveness of CNCs-GMA@PAAm was measured by UV spectroscopy and compared with that of pure CNCs. Figure 7 The results show that CNCs-GMA@PAAm is solvent responsive.

[0041] Preparation of CNCs-GMA@PPAm-FPBA: Photoinitiation strategy in polyacrylamide hydrogel three-dimensional networks FPBA interacts with glucose

[0042] Take the prepared CNCs-GMA optical film and place it in a polystyrene plastic dish with a radius of 2 cm for later use, keep AAm, Bis and PI in the same proportion as above, add 200 mg (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, and fully dissolve the mixture in DMSO to obtain a hydrogel monomer solution. Fully soak the prepared CNCs-GMA optical film in pure DMSO solution and a hydrogel monomer solution containing FPBA, respectively, and suck out the excess solution with a plastic dropper. Irradiate the fully soaked film under ultraviolet light to achieve photo-initiated polymerization, and obtain an optical composite material containing FPBA after drying.

[0043] In the glucose stimulation responsiveness test of CNCs-GMA@PAAm-FPBA, 1mM, 5mM and 10mM glucose water / ethanol mixed solutions (ethanol content 75%) were prepared respectively, and the color change of the photonic crystal gel was recorded every 30s. The solution was slowly dripped onto the surface of the CNCs-GMA@PAAm-FPBA material drop by drop to observe the responsiveness. The results are shown in Figure 2. Figure 8 As shown. The response results show that CNCs-GMA@PAAm-FPBA always maintains a blue-green color in pure water / ethanol composite solvents without glucose. When the material is stimulated by 1mM glucose solution, the color of the material changes from blue to blue-green at 30s, indicating a certain degree of red shift. The color of the material changes to green at 60s, and the colors are yellow and red-orange at 90s and 120s respectively; when the material is stimulated by 5mM glucose solution, the material shows red at 90s; when the material is stimulated by 10mM glucose solution, the time for the material color to reach red is shortened to 60s, and then it remains red and reaches equilibrium.

[0044] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. A CNCs modification method, characterized in that: The CNCs modification method comprises the following steps: S1, preparing a CNCs aqueous solution; and S2, GMA is added to the CNCs aqueous solution for chemical modification. The hydroxyl groups of CNCs react with the epoxy groups of GMA to undergo a ring-opening reaction, so that GMA is grafted onto the surface of CNCs to form a CNCs-GMA aqueous solution. The carbon-carbon double bond of GMA is retained and introduced into the CNCs-GMA structure.

2. The CNCs modification method according to claim 1, characterized in that: The step S1 includes the following sub-steps: S11, the amorphous regions in the cellulose raw material are hydrolyzed by sulfuric acid, leaving the crystalline regions to provide the basis for the formation of CNCs; S12, dialysis to remove excess sulfuric acid and small molecule impurities; as well as S13, centrifugation to remove incompletely hydrolyzed cellulose raw materials.

3. The CNCs modification method according to claim 1, characterized in that: The CNCs aqueous solution in step S1 self-assembles into a CNCs optical film with a cholesteric liquid crystal structure.

4. The CNCs modification method according to claim 1, characterized in that: In the step S2, acid is added to the CNCs aqueous solution to adjust its pH to 3.0, and then GMA is added, and the mixture is mixed and stirred to obtain a CNCs-GMA aqueous solution.

5. The CNCs modification method according to claim 1, characterized in that: The CNCs modification method also includes adding AAm to the CNCs-GMA aqueous solution for copolymerization and co-assembly, and introducing CNCs into the three-dimensional network of polyacrylamide hydrogel to obtain CNCs-GMA@PAAm.

6. The CNCs modification method according to claim 5, characterized in that: AAm, Bis and PI were dissolved in CNCs-GMA aqueous solution, co-assembled by volatilization induction, and then irradiated under ultraviolet light to achieve photopolymerization to obtain CNCs-GMA@PPAm gel material.

7. The CNCs modification method according to claim 1, characterized in that: In the step S2, the CNCs-GMA aqueous solution is induced to self-assemble to prepare a CNCs-GMA optical film through volatilization.

8. The CNCs modification method according to claim 7, characterized in that: The CNCs modification method also includes introducing FPBA that interacts with glucose into the three-dimensional network of polyacrylamide hydrogel using a photoinitiator strategy to obtain CNCs-GMA@PAAm-FPBA.

9. The CNCs modification method according to claim 8, characterized in that: AAm, Bis, PI and FPBA were added to DMSO and dissolved to obtain a hydrogel monomer solution containing FPBA. The CNCs-GMA optical film was fully immersed and swelled in pure DMSO solution and a hydrogel monomer solution containing FPBA, respectively, and irradiated under ultraviolet light to achieve photoinitiated polymerization. After drying, the CNCs-GMA@PAAm-FPBA optical composite material was obtained.

10. The CNCs modification method according to claim 6 or 9, characterized in that: The mass ratio of AAm, Bis and PI is 100:10:1.

Citation Information

Patent Citations

  • Novel nano-crystalline cellulose graft modification method

    CN104877083A

  • Preparation method of photocrosslinked polyvinyl alcohol / nanocrystal cellulose (PVA / CNC) composite film

    CN105820356A

  • Method for preparing aquagel by using grape residue extract based composite material

    CN110511403A

  • Cellulose nanocrystal-polyacrylamide double-network hydrogel and preparation method thereof

    CN110591119A

  • Method for preparation of self-repairing formaldehyde-removing polyurethane water-based paint from grape residue

    CN110628313A